Responsibilizing individuals, regulating health: debating public spots, risk, and neoliberal governmentality in contemporary Turkey - AYKAN BENTAHAR, BAHAR (CAMBRIDGE UNIV PRESS, 2015)
Currently, a mass media campaign is underway in Turkey using a new communication means called the public spot (kamu spotu). This article concentrates on the public spots produced by Turkey's Ministry of Health, and more specifically on those that advocate quitting smoking and preventing obesity. Drawing on interviews with Ministry of Health personnel and analyzing the content of these spots, we suggest that they operate as risk caveats. They caution individuals against smoking and obesity's potential harms and guide her/him towards self-health governance by encouraging the maintenance of a particular lifestyle that embraces a balanced diet, regular activity, and no smoking. As such, we read these spots as a technique of neoliberal governmentality. This technique works primarily by responsibilizing individuals as health entrepreneurs investing in risk free lifestyles; that is, by conceptualizing health as a matter of self-conduct where personal responsibilities are emphasized.
Keywords: Neoliberal governmentality; responsibilization; health governance; public spots; Turkey; ANTISMOKING CAMPAIGNS; NEO-LIBERALISM; BIO-POLITICS; TERRORISM; BODY